Achieving regional growth dynamics in African agriculture: past lessons and future challenges - Abdulai, Awudu; Diao, Xinshen; Johnson, Michael E. (International Food Policy Research Institute, 2005)
This study focuses on public investments and policy reforms for leveraging growth spillovers at the African regional level. A conceptual framework that is built on the endogenous growth theory and the new economic geography is presented first to gain a better understanding of the underlying theory and empirical evidence on regional integration and growth spillovers. In order to demonstrate the potential benefits from greater cross-border technology spillovers in Africa, as well as from trade liberalization and investment in infrastructure, results from ex-ante simulations using partial and general equilibrium models are then presented and discussed. Results indicate that sizeable regional spillover benefits can be obtained by permitting greater crossborder transfer and adoption of improved technologies, sometimes as large as three to four times the gain in direct benefits obtained within the innovating countries. This is especially true for commodities like mutton, groundnuts and sorghum. Moreover, reducing trade barriers between African countries in agriculture and non-agriculture can significantly increase intra-regional agricultural trade and raise economic growth rates. The simulations also demonstrate that improving transportation infrastructure generates the most encouraging results, increasing agricultural income by as much as 10%. The findings in this study confirm that greater regional cooperation in agricultural research and development, harmonization of regulatory standards for technology adaptation, and harmonization and liberalization of trade systems within the region could play a crucial role in expanding opportunities for African farmers. Therefore, strengthening linkages among African countries through infrastructure, agricultural R&D, and expansion of intraregional trade can generate large spillovers and leverage regional growth.